Determinants of Inflation in Indonesia: Do Changes in World Oil Prices Matter? - Putri, Defani Ivena; Arintoko, Arintoko; Kadarwati, Nunik; Firdauzi, Indrawan (Journal of Economics Research and Social Sciences, 2024)
This research was conducted to investigate the effect of world oil prices, interest rates, and money supply on inflation in Indonesia. This study uses the Autoregressive Distributed Lag (ARDL) analysis method. The data used were monthly data from January 2014-May to 2022. The results show that interest rates do not significantly affect inflation in the short or long run. Money supply has a negative relationship with inflation in the short and long run. In the short term, world oil prices have a negative effect on inflation. Meanwhile, world oil prices have a positive and significant relationship with inflation in the long run. This finding implies that it is necessary to emphasize policies other than interest rates when controlling inflation, such as more straightforward bureaucratic policies, ease of investment services, and a more effective import trading system. Bank Indonesia should also remain consistent and focus on prudence when implementing macroeconomic policies. The government must also consider the timeframe for determining the oil price policy because it has different short-term and long-term effects.